Aesthetic evaluation and the perceived properties of Chinese characters - Qinjing Zhang; Hiroyuki Mitsudo (PLoS ONE, 2025)
Previous studies have indicated that the visually perceived properties of geometrical figures influence aesthetic evaluations. However, it is unclear whether findings based on geometrical figures can be extended to artworks such as paintings and calligraphy, as artworks have their own contents and meanings. To answer this question, we designed experiments in which users of Chinese characters were asked to rate the perceived symmetry, complexity, prototypicality, and beauty of Chinese characters. Each character was presented to 35 Japanese and Chinese participants in five typing fonts in a laboratory setting (Experiment 1), and to 100 Japanese participants in five calligraphic handwriting scripts online (Experiment 2). By analyzing the relative impacts of perceived properties on aesthetic evaluation and their interactions with script styles using a generalized linear mixed model, we discovered that script style plays an important role in the association between the perceived properties and aesthetic evaluation of Chinese characters. These results are discussed in relation to studies on the aesthetic evaluation of geometrical figures and recent studies using Chinese calligraphy.